Holmium Yttrium-Aluminum-Garnet Laser Lithotripsy: An Effective Endoscopic Treatment for Bouveret’s Syndrome - Hasan Selim Güler,; Oğuz Üsküdar, (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Güler HS, Üsküdar O. Holmium yttrium-aluminum-garnet laser lithotripsy: An effective endoscopic treatment for Bouveret’s syndrome. Turk J Gastroenterol. 2024;35(3):262-263.